Incorporation of beads into oral films for buccal and oral delivery of bioactive molecules - Castro, Pedro M. (2018)
The association of alginate beads and guar-gum films in a single delivery system was idealized to promote a more effective buccal and oral delivery of bioactive molecules. A response surface method (experimental design approach) was performed to obtain optimal formulations of alginate beads to be incorporated into guar gum oral films as combined buccal and oral delivery systems for caffeine delivery. The combined formulation was further characterized regarding physicochemical properties, drug release, cell viability and buccal permeability. Beads average size, determined by dynamic light scattering (DLS), was of 3.37 ± 6.36 μm. Film thickness was set to 62 μm. Scanning electron microscopy micrographs revealed that beads were evenly distributed onto the film matrix and beads size was in accordance to data obtained from DLS analysis. Evaluation of Fourier-transform infrared spectra did not indicate the formation of new covalent bonds between the matrix of guar-gum films, alginate beads and caffeine. In vitro release assays by dialysis membrane allowed understanding that the combination of guar-gum films and alginate beads assure a slower release of caffeine when compared with the delivery profile of free caffeine from alginate beads or guar-gum films alone. MTT assay, performed on human buccal carcinoma TR146 cell line, allowed concluding that neither guar-gum film, alginate beads nor guar-gum film incorporated into alginate beads significantly compromised cell viability after 12 h of exposure. As demonstrated by in vitro permeability assay using TR146 human buccal carcinoma cell lines, combination of guargum films and alginate beads also promoted a slower release and, thus, lower apparent permeability (1.15E–05 ± 3.50E-06) than for caffeine solution (2.68E–05 ± 7.30E-06), guar-gum film (3.12E–05 ± 4.70E-06) or alginate beads (2.01E–05 ± 3.90E-06). The conjugation of alginate beads within an orodispersible film matrix represents an effective oral/buccal delivery system that induces a controlled release along with an enhanced intimate contact with cell layers that may promote higher in vivo bioavailability of carried drugs.